2006
DOI: 10.4314/thrb.v8i1.14262
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the endemicity of plague in Karatu and Ngorongoro, northern Tanzania

Abstract: Commensal and field rodents and wild small carnivores were live-trapped in five villages of Karatu district and one settlement in the Ngorongoro Conservation Area in Ngorongoro district in Tanzania. Blood samples were taken and serologically tested for plague, using the Blocking ELISA technique. Some domestic dogs and cats in the Karatu villages were aseptically bled and similarly tested for plague. Fleas were collected from the examined animals and from randomly selected residential houses. A total of 241 rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 3 publications
3
40
0
Order By: Relevance
“…This increase appears to be largely driven by the high numbers of M. natalensis found in agricultural habitats, with the abundance of this species being very strongly correlated to plague seroprevalence. Mastomys natalensis is one of the most frequently seropositive species for Y. pestis in Africa and is a widespread commensal species 38,59 (and an important host of various other human pathogens, including Lassa virus 60,61 ). Analogous changes in community composition, with a common commensal species serving as a major reservoir and "key host" for a pathogen, have been reported elsewhere, Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase appears to be largely driven by the high numbers of M. natalensis found in agricultural habitats, with the abundance of this species being very strongly correlated to plague seroprevalence. Mastomys natalensis is one of the most frequently seropositive species for Y. pestis in Africa and is a widespread commensal species 38,59 (and an important host of various other human pathogens, including Lassa virus 60,61 ). Analogous changes in community composition, with a common commensal species serving as a major reservoir and "key host" for a pathogen, have been reported elsewhere, Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our host community model should accommodate incomplete sampling, and the species-specific seroprevalence patterns observed in the rodents sampled in this study are compatible with other surveys of rodent seroprevalence in the same region. 38 Also, although seroprevalence studies are widely adopted for plague surveillance, we note that plague seroprevalence studies offer insights into rates of Y. pestis resistance rather than infection or infectiousness, that is, animals that die of Y. pestis infection are not available to sample. Can M. natalensis act as infectious plague hosts, or do they simply exhibit resistance to infection and not play a part in infecting fleas?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A historical report from Tanzania described severe tungiasis in pigs [14]. Recently, Kilonzo et al (2006) identified Tunga penetrans fleas inside dwellings in northern Tanzania [15].…”
Section: Discussionmentioning
confidence: 99%
“…96 Since 1983, outbreaks of human plague have occurred almost nonstop, which had not been the case for the previous 30-year period. 18,23,24,32,[50][51][52]66,67,78,85,[97][98][99][100][101][102] In Uganda, the earliest documented cases of plague were recorded by missionaries in 1877. 103 During the first half of the 20th century, the main plague foci in Uganda were localized in the Ituri forest, around Lake Albert, Burungu Island in Lake Victoria, Rubaga hill near Kampala and the Kyaggwe areas in the districts of Mukono, Masaka, Rakai, Pallisa, Tororo, and Busia.…”
Section: Lotfymentioning
confidence: 99%